Answer:
(x + 20)(x + 11)
Explanation:
x(x + 20) + 11(x + 20) =
Factor out the common factor of x + 20.
= (x + 20)(x + 11)
The binomials make it look complicated, but this is simpler than you think.
Look at this simpler, but similar, example.
Factor xy + 4y
xy + 4y =
You see clearly that y is a common factor, so you factor out y, and you get
= y(x + 4)
In your problem, you have
x(x + 20) + 11(x + 20) =
where (x + 20) is the common factor.
You factor out the common factor, (x + 20). What is left? x + 11 as a factor, so you get
(x + 20)(x + 11)